Pemanfaatan Aplikasi Online untuk Ujian Akhir Mahasiswa Berbasis Website pada Program Studi Diploma-3 Teknik Telekomunikasi Politeknik Negeri Ujung Pandang - Sandryones Palinggi; Riesa Krisna Astuti Sakir; Sufianti Munirman (Universitas Pahlawan Tuanku Tambusai, 2022)
Learning in the Industrial Revolution 4.0 era indirectly encourages overall changes in the teaching and learning process. The evolution that has occurred has had a big impact so it is hoped that teaching staff and students will be more skilled in using digital platforms as learning media. This research aims to design and gain benefits from online applications for Website-based Final Semester Examinations. With the issue of using single-use paper in the Final Exam for Students of the D3 Telecommunications Engineering Study Program at State Polytechnic of Ujung Pandang, it can be resolved by using a website-based application in implementing the Final Exam as a solution that can be implemented later. The method used in this research is the development method or Research and Development (R&D), where this method focuses on developing an application, or modifying it, so that the objectives of this research can be achieved. The intended application design aims to make it easier for students to access and carry out various types of activities on a website portal that can be controlled and monitored. In completing this research, Moodle was chosen to resolve an issue that was raised, and it is hoped that it can be the right solution as a concrete step for the contribution of lecturers, especially in resolving issues related to the continued use of single-use paper in the final semester exams for students of the D3 Telecommunications Engineering Study Program. From the issues raised, the use of online applications for website-based student final exams in the D3 Telecommunications Engineering Study Program is a solution that can be implemented as soon as possible.